2016
DOI: 10.1080/02650487.2015.1128868
|View full text |Cite
|
Sign up to set email alerts
|

Is there gender bias when creative directors judge advertising? Name cue effect in ad evaluation

Abstract: A lack of women in creative departments has been documented in previous research. These departments are seen as a male fraternity subculture in advertising agencies, where women experience many difficulties in their career progress. One of these drawbacks is gender bias in the selection of ideas' process. Male creative directors are believed to promote ideas created by men within a homosocial environment. This female perception, that emerged from previous qualitative research, is studied experimentally for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
1
0
1
Order By: Relevance
“…La perspectiva del anunciante como público objetivo de la comunicación es prácticamente inexistente. La evaluación de la creatividad ha sido estudiada básicamente desde el punto de vista de los creativos o propios profesionales de la publicidad (Roca, Tena, Lázaro & González, 2016;West, Christodoulides & Bonhomme, 2018) o de los consumidores (Chang, 2014;Lehnert, Till & Ospina, 2014;Reinartz & Saffert, 2013) pero no encontramos referencias desde el punto de vista del anunciante.…”
Section: Monográficounclassified
“…La perspectiva del anunciante como público objetivo de la comunicación es prácticamente inexistente. La evaluación de la creatividad ha sido estudiada básicamente desde el punto de vista de los creativos o propios profesionales de la publicidad (Roca, Tena, Lázaro & González, 2016;West, Christodoulides & Bonhomme, 2018) o de los consumidores (Chang, 2014;Lehnert, Till & Ospina, 2014;Reinartz & Saffert, 2013) pero no encontramos referencias desde el punto de vista del anunciante.…”
Section: Monográficounclassified
“…The authors found that, consistent with prior research, that clients themselves need to be cognizant of trade-offs that may be present between originality and achieving strategic goals. While not studied from both the client and agency side, recent studies have looked at whether gender issues may affect campaign evaluations (e.g., Infanger and Sczesny 2015;Roca et al 2016).…”
mentioning
confidence: 99%